2022
DOI: 10.1186/s12884-022-05253-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical-epidemiological characteristics and maternal-foetal outcomes in pregnant women hospitalised with COVID-19 in Venezuela: a retrospective study

Abstract: Background In low- and middle-income countries, pregnant women and newborns are more vulnerable to adverse outcomes from coronavirus disease 2019 (COVID-19). However, in Venezuela, there are no integrated data in a national surveillance system to identify the clinical-epidemiological characteristics and maternal-foetal outcomes of pregnant women hospitalised with COVID-19. Methods A retrospective study was conducted among Venezuelan pregnant women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…On the other hand, while the clinical behavior of patients with COVID-19 during the first wave in Venezuela showed a high overall and in-hospital mortality [ 30 ], the clinical outcome of the first locally recorded pregnant woman infected with SARS-CoV-2 and her child was favorable [ 31 ]. However, two recent studies reported a high prevalence of maternal–fetal events among Venezuelan pregnant women with COVID-19 [ 32 , 33 ]. Therefore, simultaneous infection with these two pathogens could create a favorable setting leading to increased maternal–fetal risk in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, while the clinical behavior of patients with COVID-19 during the first wave in Venezuela showed a high overall and in-hospital mortality [ 30 ], the clinical outcome of the first locally recorded pregnant woman infected with SARS-CoV-2 and her child was favorable [ 31 ]. However, two recent studies reported a high prevalence of maternal–fetal events among Venezuelan pregnant women with COVID-19 [ 32 , 33 ]. Therefore, simultaneous infection with these two pathogens could create a favorable setting leading to increased maternal–fetal risk in pregnant women.…”
Section: Discussionmentioning
confidence: 99%